Is cerebral salt wasting related to sympathetic dysregulation in tuberculous meningitis?. (16th March 2021) - Tripathi, Abhilasha; Thakur, Ravindra Singh; Kalita, Jayantee; Patel, Devendra Kumar; Misra, Usha K.
Highlights: TBM patients with CSW had significantly higher levels of catecholamines. Significant alteration in catecholamine levels was observed in sequential study. Dopamine and epinephrine were related to severity of TBM and CSW respectively. Results provide evidence of adrenergic activity in the pathogenesis of CSW in TBM. Abstract: Background: Cerebral Salt wasting ( CSW) is common in Tuberculous Meningitis (TBM) and is suggested to be due to sympathetic dysregulation of renal blood supply but has not been proven. Objective: To evaluate plasma Catecholamines in TBM patients with CSW and correlate with the markers of stress. Materials and methods: The diagnosis of TBM was based on clinical, CSF and MRI criteria. Catecholamines level was measured by LC–MS on admission, at the time of hyponatremia and on correction of hyponatremia. Catecholamine levels were correlated with clinical and laboratory markers of stress, hyponatremia and severity of CSW using pre-defined criteria. Results: There were 24 patients with TBM (12 with CSW) and 12 controls. The median age of patients was 31 (18−75) years and 12 (50 %) were females. TBM patients with CSW had significantly higher levels of catecholamines compared to controls (p < 0.001). TBM patients with CSW had higher levels of norepinephrine than those without CSW (p = 0.034). Sequential studies revealed that dopamine and epinephrine increased at the time of hyponatremia and declined on its correction. Severity of TBM was related to dopamine (p = 0.04) and severity of CSW was related to epinephrine (p = 0.016). Conclusion: CSW in TBM seems to be related to catecholamine dysregulation.